A comparative study to assess the effects of intrathecal fentanyl and intrathecal tramadol combined with 0.5% bupivacaine heavy in patients undergoing elective urological surgeries: A prospective randomized study - Baig Mirza Wajeed,; Manmohan Jindal,; Neelima Tandon,; Namrata Jain,; Mahesh Kumar Vishwakarma, (Asian Journal of Medical Sciences, 2024)
Background: Urological operations frequently involve the use of spinal anesthesia. In the present scenario, adding different adjuvants to local anesthetic improve its quality and duration has become common. Aims and Objectives: In patients undergoing elective urological procedures, the purpose of this study was to assess the effects of intrathecal fentanyl or tramadol with 0.5% bupivacaine heavy. Materials and Methods: Patients were divided into two groups of 30 patients each, a total of 60 patients aged 20–60 years undergoing elective urological surgeries participated in this prospective, randomized study in which 25 μg fentanyl and 2.5 mL of 0.5% bupivacaine heavy were given to Group F, while 25 mg tramadol and 2.5 mL of 0.5% bupivacaine heavy were given to Group M. The onset and duration of sensory and motor blockage, the duration of analgesia, post-operative Visual Analog Scale score, hemodynamic changes, and adverse effects were evaluated. Results: Fentanyl had a lower mean time of onset for sensory (2:33±0:22 min vs. 4:50±0:33 min) and motor block (3:36±0:28 min vs. 5:52±0:38 min) (P<0.001), the duration of sensory (185.67±3.155 min vs. 152.60±4.264), motor block (172.00±4.177 min vs. 136.40±5.575 min), and post-operative analgesia was longer in the fentanyl group (P<0.001), whereas the incidence of adverse effects such as pruritus, shivering, and nausea was lower in the tramadol group. Conclusion: The quality and duration of spinal anesthesia were found to be significantly increased by the use of fentanyl as an adjuvant in our study. However, tramadol also produced stable hemodynamics and exhibited fewer adverse effects than fentanyl.